Sexual and reproductive health mobile apps: results from a cross-sectional values and preferences survey to inform World Health Organization normative guidance on self-care interventions. Issue 1 (31st December 2020) - Logie, Carmen; Okumu, Moses; Abela, Heather; Wilson, David; Narasimhan, Manjulaa
ABSTRACT: Mobile application (app) platforms have the potential to advance sexual and reproductive health (SRH). Yet there is a dearth of knowledge regarding global perspectives from healthcare providers on how SRH mobile apps are being leveraged in their healthcare practice. In 2019 the World Health Organization (WHO) developed a consolidated guideline on self-care interventions for SRH. To inform this guideline, we conducted a global values and preferences survey. This study aimed to (a) understand the awareness, access, and uptake of SRH mobile apps; (b) examine how many healthcare provider (HCP) participants provided linkages, referrals and information to clients regarding SRH mobile apps; and (c) among HCP, assess how many felt confident and informed regarding SRH mobile apps. We hosted a cross-sectional web-based survey on the WHO Department of Reproductive Health and Research website and shared the survey with SRHR listservs. There were 825 survey participants, 360 whom identified as healthcare providers (HCP). Approximately one-third of HCP participants had provided a referral/information to their clients about sexual or reproductive health apps. While 40.8% of HCP felt confident and informed about sexual health apps, half (47.4%) reported needing more information, and 15.6% expressed interest in receiving training to use in practice. While 42.6% of HCPs felt confident and informed about reproductive health apps, 45.7% needed more information, and 15.1% were interested in further training. There was also an open-ended question for HCP to share their thoughts about self-care SRH interventions. Specifically regarding SRH apps, HCP responses revealed the importance of considering: (a) security and confidentiality; (b) potential benefits of SRH apps for underserved groups (i.e. youth, rural communities); (c) community engagement; (d) health benefits; and (e) and online training for HCP on SRH mobile apps. Findings signal interest and opportunities for training and engaging HCP in using mobile apps to advance SRH.